The role of teachers in the development of verbal communication in elementary school students - Muhammad Rayyan Arief Syah; Dyah Lyesmaya; Utomo; Annisa Dzahira Shofa (Universitas Kanjuruhan Malang, 2026)
This study evaluates students' verbal communication skills, identifying the efforts and roles of teachers at SDN Cijambe Tengah. Using a qualitative case study, data were collected through observation, semi-structured interviews, and documentation involving 6 teachers and 36 students selected purposively. Data were analyzed using the Interactive Analysis Model. Findings indicate that students' verbal communication skills vary widely, reflecting diverse family socioeconomic backgrounds. Teachers stimulate these skills through emotional approaches, storytelling, small group discussions, and equitable support to eliminate the dominance of active students. In conclusion, findings indicate that teachers fulfill important roles as facilitators, motivators, counselors, and humanistic role models. Their efforts demonstrate the potential to transform communication anxiety into self-confidence, while aligning language development with the formation of students' moral character both at school and at home.